Poxviral promoters for improving the immunogenicity of MVA delivered vaccines - Naif Khalaf Alharbi (Taylor & Francis Group, 2019)
Modified vaccinia virus Ankara (MVA) is a replication-deficient poxvirus, attenuated in chick embryo fibroblast primary cells. It has been utilised as a viral vector to develop many vaccines against cancer and infectious diseases such as malaria, HIV/AIDS, influenza, and tuberculosis, MERS-CoV, and Ebola virus infection. There is accumulating data from many preclinical and clinical studies that highlights the excellent safety and immunogenicity of MVA. However, due to the complex nature of many pathogens and their pathogenicity, MVA vectored vaccine candidates need to be optimised to improve their immunogenicity. One of the main approaches to improve MVA immunogenicity focuses on optimising poxviral promoters that drive recombinant vaccine antigens, encoded within recombinant MVA vector genome. A number of promoters were described or optimised to improve the development of MVA based vaccines such as p7.5, pF11, and mH5 promoters. This review focuses on poxviral promoters, their optimisation, genetic stability, and clinical use.